The Role of Patient Satisfaction as a Mediating Variable in the Influence of Outpatient Registration Service Quality on Patient Loyalty of BPJS Non-PBI Participants at Hospital "X" in Tulangan District, Sidoarjo Regency in 2023-2024 - Eka Gusti, Titis; Iva Afkarina, Iin (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
One measure of the quality of health services is a survey of patient satisfaction. Good quality health services will have an impact on their loyal attitude. Increased loyalty proves that medical services are acceptable and recognized for their quality. The aim of this research is to analyze the reciprocal relationship between the quality of outpatient registration services and the loyalty of non-PBI BPJS participant patients through satisfaction levels at Aisyiyah Fatimah Tulangan Sidoarjo Hospital in 2023–2024. This research method is quantitative analytical and the design approach is cross sectional. The sample used was 96 respondents using purposive sampling. Data analysis is path analysis with multiple linear regression statistical tests. The research test results were obtained from the analysis of the influence of service quality on patient loyalty with a p-value of (0.000), service quality had an influence on patient satisfaction with a p-value of (0.000), a p-value of (0.000) on the influence of satisfaction on patient loyalty and test the effect of service quality on loyalty through patient satisfaction p-value (0.001). It is known that the R-square of the variables of service quality, patient satisfaction and loyalty is 0.530. In this research, it was found that there was an influence of service quality variables on patient loyalty which was mediated by patient satisfaction variables with a percentage contribution level of influence of 53%.